ENVIRONMENTAL CONSERVATION ACTION THROUGH COMMUNITY-BASED MANGROVE SEEDLING PLANTING IN EDUCATION AND SOCIETY: THE FOLU GOES TO SCHOOL - Baunsele, Since Dortia; Nitti, Fidelis; Wolo, Daniel (LPPM Universitas Flores, 2026)
This community service activity aims to enhance students' and community members' knowledge, awareness, and participation in climate change mitigation efforts through socialization and mangrove seedling planting. The selection of mangrove seedling planting locations is based on observations of degrading mangrove forests that still have the potential for natural regeneration. In addition, the location is prioritized in areas experiencing anthropogenic pressure, coastal erosion, and excessive sedimentation. Socio-economic considerations are also a key factor. The planting location is close to residential areas to encourage public participation and environmental awareness. This activity is carried out in the mangrove forest tourism area, Oesapa village, Kelapa Lima sub-district, Kupang City, over a period of 2 months, namely November – December. The method for implementing the activity consists of three stages: socializing students about the role of mangrove forests; cleaning the area with the surrounding community; planting mangrove seedlings; and initial maintenance and monitoring. In addition to increasing knowledge and awareness of mangrove forests' functions, this activity also contributes to the rehabilitation of mangrove areas. It strengthens collaboration among students, the community, the government, and academics in the effort to preserve mangrove forests.